Highly Charged Ruthenium(II) Polypyridyl Complexes as Lysosome‐Localized Photosensitizers for Two‐Photon Photodynamic Therapy. (8th October 2015) - Huang, Huaiyi; Yu, Bole; Zhang, Pingyu; Huang, Juanjuan; Chen, Yu; Gasser, Gilles; Ji, Liangnian; Chao, Hui
Abstract: Photodynamic therapy (PDT) is a noninvasive medical technique that has received increasing attention over the last years and been applied for the treatment of certain types of cancer. However, the currently clinically used PDT agents have several limitations, such as low water solubility, poor photostability, and limited selectivity towards cancer cells, aside from having very low two‐photon cross‐sections around 800 nm, which limits their potential use in TP‐PDT. To tackle these drawbacks, three highly positively charged ruthenium(II) polypyridyl complexes were synthesized. These complexes selectively localize in the lysosomes, an ideal localization for PDT purposes. One of these complexes showed an impressive phototoxicity index upon irradiation at 800 nm in 3D HeLa multicellular tumor spheroids and thus holds great promise for applications in two‐photon photodynamic therapy. Abstract : Sehr positiv : Die Titelkomplexe können in der photodynamischen Therapie (PDT) eingesetzt werden. Sie sammeln sich durch Endozytose selektiv in Lysosomen und zeichnen sich bei Bestrahlung mit einem Zwei‐Photonen‐Laser durch eine hohe Phototoxizität gegenüber zweidimensionalen Monoschicht‐Krebszellen und dreidimensionalen multizellulären Tumorsphäroiden aus.